One-dimensional model equations for hyperbolic fluid flow. (July 2016) - Do, Tam; Hoang, Vu; Radosz, Maria; Xu, Xiaoqian
Abstract: In this paper we study the singularity formation for two nonlocal 1D active scalar equations, focusing on the hyperbolic flow scenario. Those 1D equations can be regarded as simplified models of some 2D fluid equations.